Establishing Better Standards of Care in Doppler Echocardiography, Computed Tomography and Nuclear Cardiology - Fleming, Richard M. (IntechOpen, 2011)
Since the introduction of Doppler Echocardiography, Nuclear Cardiology and Coronary CT imaging, clinicians and researchers have been searching for ways to improve their use of these important tools in both the diagnosis and treatment of heart disease. To keep up with cutting edge improvements in these fields, experts from around the world have come together in this book to provide the reader with the most up to date information to explain how, why and when these different non-invasive imaging tools should be used. This book will not only serve its reader well today but well into the future.